2020
DOI: 10.1111/jocn.15393
|View full text |Cite
|
Sign up to set email alerts
|

Health specialists’ views on the needs for developing a digital gaming solution for paediatric day surgery: A qualitative study

Abstract: Aims and objectives To describe the views on the needs of health specialists to consider when developing a digital gaming solution for children and families in a paediatric day surgery. Background Children's day surgery treatment is often cancelled at the last minute for various reasons, for example due to the lack of information. Digital gaming solutions could help families to be better oriented to the coming treatment. Despite the increasing demands for mHealth systems, there is not enough evidence‐based inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 35 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…However, parents and in some cases children, need to be provided with written information concerning the pre‐, intra‐ and postoperative phases of the treatment to enhance their knowledge (Landier et al., 2018 ). The information should be in the person's own language (Rantala, Pikkarainen, & Pölkki, 2020 ) and, when provided to children, based on their age and understanding (EACH, 2016 ; Quaye et al., 2019 ). Several mHealth studies describe the development of web‐based games that prepare children for their surgery (Buffel et al., 2019 ; Chow et al, 2017 ), with several examples of approaches using virtual reality (Al‐Nerabieah et al., 2020 ; Jung et al., 2021 ).…”
Section: Backroundmentioning
confidence: 99%
See 4 more Smart Citations
“…However, parents and in some cases children, need to be provided with written information concerning the pre‐, intra‐ and postoperative phases of the treatment to enhance their knowledge (Landier et al., 2018 ). The information should be in the person's own language (Rantala, Pikkarainen, & Pölkki, 2020 ) and, when provided to children, based on their age and understanding (EACH, 2016 ; Quaye et al., 2019 ). Several mHealth studies describe the development of web‐based games that prepare children for their surgery (Buffel et al., 2019 ; Chow et al, 2017 ), with several examples of approaches using virtual reality (Al‐Nerabieah et al., 2020 ; Jung et al., 2021 ).…”
Section: Backroundmentioning
confidence: 99%
“…On the other hand, a systematic review and meta‐analysis (Rantala et al., 2020 ) showed that web‐based mobile health interventions, including video clips, web‐based treatment preparation interventions and games, can reduce children's pre‐operative anxiety and increase parental satisfaction, but did not report whether these approaches were effective at reducing children's pain after day surgery treatment. According to Rantala, Pikkarainen, and Pölkki ( 2020 ), health care personnel could integrate gamification into the patient journey with the objective of increasing patients' commitment to their treatment and enabling communication between personnel and patients before a hospital visit (Rantala, Pikkarainen, & Pölkki, 2020 ). Considering the parent's view, a digital gamified solution should support the care of children, prepare both parents and children for the upcoming treatment and increase children's commitment to care (Rantala, Jansson, et al., 2020 ).…”
Section: Backroundmentioning
confidence: 99%
See 3 more Smart Citations